Pengaruh Adversity Quotient dan Prokrastinasi Akademik Terhadap Prestasi Akademik - Yolanda, Yolanda; Susanti, Dessi (Jurnal Ecogen, 2024)
This research aims to analyze 1) The impact of the adversity quotient and academic procrastination on students' academic achievement at Faculty of Economics and Business Universitas Negeri Padang 2) The impact of the adversity quotient on students' academic achievement at Faculty of Economics and Business Universitas Negeri Padang 3) The impact of academic procrastination on students' achievement at Faculty of Economics and Business Universitas Negeri Padang. This study employs a quantitative methodology and is causal associative in nature. A sample of 88 respondents was selected by proportionate random sampling procedures from among the 684 active undergraduate students in the class of 2017–2019 at Faculty of Economics and Business Universitas Negeri Padang. Applying methods from multiple linear regression analysis with SPSS version 27. The research result show that  adversity quotient and academic procrastination have a significant impact of 32% on students' academic achievement at Faculty of Economics and Business  Universitas Negeri Padang